PENGARUH SISTEM AKUNTANSI DIGITAL TERHADAP PENGAMBILAN KEPUTUSAN DENGAN BUDAYA PENGAMBILAN KEPUTUSAN ANALITIS SEBAGAI VARIABEL MODERASI - Ashsifa, Izza; Mulyani, Ulva Rizky (Jurnal Akuntansi dan Bisnis, 2022)
The increasing development of digital accounting systems has increased its influence on the decision-making quality. This study aims to examine the effect of the success factors of the digital accounting system on the advancement of the decision-making quality in the banking sector in Indonesia. Questionnaires were sent to 98 decision makers who are actual users of the digital accounting system. A quantitative research approach was adopted to examine the proposed research model using SEM-PLS. The results of the study show that the information quality has a significant impact on the overall quality of decision making with digital accounting systems, while data quality and system quality have an insignificant impact. The results also show that information quality has mediated the relationship between data quality and system quality on the decision-making quality. Analytical decision-making culture has strengthened the relationship between information quality and decision-making quality. This research will provide interesting implications and recommendations for practitioners, accounting managers and decision makers about evaluating the influence of digital accounting systems on improving the quality of decision making in the banking sector in Indonesia. Keywords: digital accounting system, decision-making quality, digitalization.